IDENTIFIKASI BIDANG GELINCIR PADA DAERAH RAWAN LONGSOR DESA SRIMARTANI, YOGYAKARTA - Muhammad Faizal Zakaria; Siti Masyithoh Maisarah (Jurnal Geofisika Eksplorasi, 2019)
Landslides are one of the disasters that often occur in Srimartani Village, Piyungan District, Yogyakarta. The biggest cause of landslides is the steep slope and the existence of a sliding plane on the slope. This study aims to identify the sliding plane on the slopes in Srimartani Village. This research was conducted using geoelectric method Wenner configuration with a: 10 m and n: 6. The data acquisition was taken in 6 lines. Data processing was done using Res2Dinv software and the result is a 2D true resistivity cross section. The results of the interpretation of the six lines indicate the existence of a sliding plane which is characterized by low resistivity contrast at the bottom and higher resistivity near the surface. Low resistivity (10 Ωm) is identified as clay rock and high resistivity ( 10 Ωm) above is identified as surface soil.